PENGARUH PELAKSANAAN PEMBELAJARAN TEMATIK INTEGRATIF DENGAN PENDEKATAN SCIENTIFIC TERHADAP AKTIVITAS BELAJAR SISWA KELAS IV SD INPRES BANGKALA III KOTA MAKASSAR - Kristiani, Kristiani; Eka Fitriana HS, Eka Fitriana HS; Jalal, Jalal (Universtas Negeri Makassar, 2023)
This study aims to determine the effect of implementing integrative thematic learning with a scientific approach to the learning activities of fourth grade students at SD Inpres Bangkala III Makassar City. This research is a quantitative research with the type of experimental research with the pre-experimental form of one group pretest-posttest design. The sample in this study was class IVB as many as 23 people consisting of 14 male students and 9 female students. The sampling technique in this study was by simple random sampling. Data collection techniques used are observation, questionnaires and documentation. Data analysis used descriptive analysis and inferential statistical analysis with the help of the SPSS version 20 computer program. The results of this study indicate that the teacher's ability to carry out integrative thematic learning with a scientific approach to student learning activities gets an average of 3.2, which means well implemented, the assessment student activity in learning gets an average of 3.0 in the good category, then for the assessment of student activity in integrative thematic learning with a scientific approach gets an average of 3.1 in the good category. As for the results of implementing integrative thematic learning with a scientific approach to the learning activities of class IVB students, the results of inferential analysis are described, where the normality test data is 0.078, the homogeneity test is 0.087 and the T test results are 0.000. So that the results of the study show that there is an effect of implementing integrative thematic learning with a scientific approach to the learning activities of fourth grade students at SD Inpres Bangkala III Makassar City.